1998
DOI: 10.1212/wnl.51.5.1359
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for intracerebral hemorrhage (STICH)

Abstract: A trial of early surgery for ICH is feasible. This study represents the largest prospective, randomized series of surgery for ICH. A modest early mortality benefit for surgery is possible, but long-term benefit for surgery was not established in this single-center pilot investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
2
13

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(164 citation statements)
references
References 9 publications
3
146
2
13
Order By: Relevance
“…To date, there are nine prospective randomized controlled studies in which surgical and medical management of SICH has been compared. 6,9,27,61,84,89,90,120,138 Overall, these studies fail to demonstrate a superiority of either medical or surgical management. The results are also limited by considerable methodological differences among the trials.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are nine prospective randomized controlled studies in which surgical and medical management of SICH has been compared. 6,9,27,61,84,89,90,120,138 Overall, these studies fail to demonstrate a superiority of either medical or surgical management. The results are also limited by considerable methodological differences among the trials.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Morganstern, et al, 90 prospectively randomized 34 patients within 12 hours of onset. They reported a modest benefit in 6-month mortality rates in patients treated with craniotomy (19%) compared with medical therapy (24%).…”
Section: Neurosurg Focus / Volume 15 / October 2003mentioning
confidence: 99%
“…We found that smaller bleeds are better managed conservatively, while optimal management of moderate and large bleeds is inconclusive and there was no difference in the outcome at the end of three months. Generally patients with significant midline shift, acute hydrocephalus and deteriorating neurological status will require surgical evacuation [12][13][14][15], however the guidelines are clear for cerebellar haematoma [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of consensus for the treatment of SICH has led to great variation in surgical and medical management [11][12][13]. Guidelines based on scant data from few randomised and many nonrandomised trials are uncertain at best [10].…”
Section: S Pontaneous Intracerebral Haemorrhage (Sich) Ismentioning
confidence: 99%
See 1 more Smart Citation